PENERAPAN POMPA HIDRAM METODE PARALEL UNTUK MENGATASI PERMASALAHAN AIR - Irkhos Irkhos; Suhendra Suhendra; Sukisno Sukisno (DHARMA RAFLESIA, 2018)
The program is implemented in Pungguk Beringin Merigi Kelindang Bengkulu Tengah. The purpose of this program is to provide the knowledge and skills of rural communities in Pungguk Beringin on utilization Hydraulic ram. Participants were representatives of community activities. The solution provided is the application of Parallel Methods Hydraulic ram. Through these program, installation Hydraulic ram diameter of 2 inches can be generated about 10 liters of effluent water in each minute with to a height of 50 meters and250 meters from water source. Some factors that can affect to this achievement are water capacity, topography, and people participation. Keywords: Hydraulic ram pump, Parallel Methods, Pungguk Beringin